Exploring Funding Models in "˜’No-Fee’’ Schools in Cape Town: Evidence from Selected Public Primary Schools. - Beyonyi, Eugene Y (American Journal of Education and Practice, 2022)
Purpose: The explicit goal of education funding policy is to raise educational standards by addressing historical financial disparities. This study, explored the funding models in three no-fees public primary schools within the Western Cape Education Department in Cape Town. The specific objective of this study was to explore and discuss the funding models' initiatives of schools in resources scarce communities in Cape Town. Methodology: A qualitative research model was adopted for the investigation. Semi-structured guided questions were used to obtain the data. Using intentional sampling, which selects individuals based on their backgrounds and expertise, a total of nine people was recruited. Three school principals, three chairs of the governing body, and three administrators of the school's finances made up the group of participants. Due to the COVID-19 pandemic, data were recorded using telephone conversations. The researcher used a thematic data analysis approach to analyse the data after recording and meticulously transcribing the talks. Individual interviews, participant data, and document analysis were all merged by the researcher in order to make the research conclusions credible. Findings: As a result, it was determined whether the information from the case study and the interviews headed in the same direction. Additionally, the researcher gave each participant a chance to confirm that the facts were what they had provided as data. The study indicated that despite receiving 75% of their income from the government, certain no-fee public primary schools still had a high level of resource reliance. A sizeable part of school funding"”25%"”comes from voluntary donations. The funding attempts, however, have not succeeded in bringing in the money the schools sorely need. Due to government rules, schools feel they have too little money left over and are unable to make significant improvements. The study also showed that fundraising campaigns have an impact on education since they interfere with class time. Additionally, the study demonstrates that learner's social competition has increased as a result of selling products on campus to raise extra money since learners whose parents cannot afford it do not want to feel afraid or humiliated. Recommendations: Selected schools should raise funds using stronger and more innovative funding initiatives rather than traditional, hands-on approaches. The government should rethink amending schooling policies to legally accord schools to collect fees, since studies show that parents in low-resource communities are removing their children from low-resource schools to well-resource schools. Governments also need to rethink school policy changes to give schools the flexibility to make significant budget changes.